Renewables in the energy transition: Evidence on solar home systems and lighting fuel choice in Kenya - Jann Lay; Janosch Ondraczek; Jana Stöver (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
We study the determinants of households' choices of lighting fuels in Kenya including the option of using solar home systems (SHS). Our goal is to add new evidence on the factors that influence the introduction and adoption of decentralized and less carbon-intensive energy sources in developing countries, and, more generally, to the empirical debate on the energy ladder. We capitalize on a unique representative survey on energy use and sources from Kenya, one of the few relatively well-established SHS markets in the world. Our results reveal some very interesting patterns of the fuel transition in the context of lighting fuel choices. While we find clear evidence for a cross-sectional energy ladder, the income threshold for modern fuel use - including solar energy use - to move beyond traditional and transitional fuels is very high. Income and education turn out to be key determinants of SHS adoption, but we also find a very pronounced effect of SHS clustering, i.e. the prevalence of SHS systems in the proximity of a potential user increases the likelihood of adoption. In addition, we do not find a negative correlation between grid access and SHS use.
Keywords: D12; O12; Q42; 330; renewable energy; household fuel choice; lighting fuel choice; solar power use; solar home systems; Kenya; energy ladder; KIHBS